Abnormal mitochondrial dynamics and impaired mitochondrial biogenesis in trigeminal ganglion neurons in a rat model of migraine. (1st January 2017) - Dong, Xin; Guan, Xinying; Chen, Keyan; Jin, Shanquan; Wang, Chengyun; Yan, Lanyun; Shi, Zhaochun; Zhang, Xue; Chen, Ling; Wan, Qi
Highlights: Defective mitochondrial morphology was detected in TG neurons in a rat model of migraine. Mitochondrial dynamics was shifted towards fission in TG neurons in a rat model of migraine. Mitochondrial biogenesis was suppressed in TG neurons in a rat model of migraine. Abstract: Accumulating evidence has demonstrated a possible role of mitochondrial dysfunction in migraine pathophysiology. Migraine sufferers exhibit impaired metabolic capacity, with an increased formation of reactive oxygen species (ROS). Mitochondrial dynamics and mitochondrial biogenesis are key processes regulating mitochondrial homeostasis. The aim of this study was to explore the alterations of mitochondrial regulatory networks in a rat model of migraine induced by repeated dural stimulation with inflammatory soup (IS). Ultrastructural, protein, gene and mitochondrial DNA analysis were applied to assess mitochondrial dynamics and biogenesis in trigeminal ganglion (TG) neurons. Mitochondria in TG neurons exhibited small and fragmented morphology after repeated dural stimulation. Further investigations showed that mitochondrial fission protein dynamin-related protein 1 (Drp1) was increased while mitochondrial fusion protein Mitofusin1 (Mfn1) was reduced in TG neurons. In addition, our results also presented that mitochondrial DNA copy number in TG neurons was reduced significantly, accompanied by alterations in mRNA and protein levels of regulatory factors related to mitochondrial biogenesis including peroxisome proliferator-activated receptor-gamma coactivator-1a (PGC-1α) and its downstream regulators in TG neurons in the IS-induced migraine model. These findings suggest that the mitochondrial dynamic regulatory networks are maladjusted in TG neurons in a rat model of migraine. Regulation of mitochondrial dynamics and biogenesis signaling may indicate a new mitochondria-targeted therapeutic strategy for migraine.